2022
DOI: 10.1055/s-0042-1758452
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Axillary Region after Excision of Hidradenitis Suppurativa: A Systematic Review

Abstract: Introduction Hidradenitis suppurativa (HS) is a chronic, debilitating, recurrent, auto-inflammatory disease of the pilosebaceous units of the skin. The axillary region is the most affected anatomical site and its reconstructive options include skin grafts, local random plasties, regional axial flaps, and regional perforator flaps. The main aim of this systematic review is to identify the best surgical technique for axillary reconstruction in the context of HS, in terms of efficacy and safety. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…However, in cases of severe conditions where patients do not respond to the aforementioned options or have irreversible lesions, surgical treatment should be considered [ 1 ]. Surgical options include skin grafts, local random flaps, regional axial flaps, regional perforator flaps, and secondary intention healing [ 13 ]. A review conducted by Amendola et al highlighted the positive outcomes of Thoracodorsal artery perforator (TDAP) flaps compared to skin grafts, showing lower recurrence rates [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in cases of severe conditions where patients do not respond to the aforementioned options or have irreversible lesions, surgical treatment should be considered [ 1 ]. Surgical options include skin grafts, local random flaps, regional axial flaps, regional perforator flaps, and secondary intention healing [ 13 ]. A review conducted by Amendola et al highlighted the positive outcomes of Thoracodorsal artery perforator (TDAP) flaps compared to skin grafts, showing lower recurrence rates [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical options include skin grafts, local random flaps, regional axial flaps, regional perforator flaps, and secondary intention healing [ 13 ]. A review conducted by Amendola et al highlighted the positive outcomes of Thoracodorsal artery perforator (TDAP) flaps compared to skin grafts, showing lower recurrence rates [ 13 ]. This is supported by the findings of Wormald et al who demonstrated in their study that patients who underwent TDAP flap reconstruction had significantly faster recovery, fewer complications, and fewer overall number of procedures than those who underwent split skin grafts (SSG) reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…We have read the review article titled “Reconstruction of the Axillary Region after Excision of Hidradenitis Suppurativa: A Systematic Review” by Amendola et al 1 While congratulating the authors on this insightful review article, we would like to contribute some insights.…”
Section: Figmentioning
confidence: 99%
“…33 Among the options for pedicled fasciocutaneous flaps, various alternatives exist, including the thoracodorsal artery perforator (TDAP), circumflex scapular artery perforator, serratus anterior thoracic artery, lateral thoracic artery perforator, lateral intercostal artery perforator, inner arm artery perforator (IAAP), and posterior arm artery perforator flaps. [34][35][36][37][38][39][40] In severe cases with extensive defects, some authors have reported the utilization of free flaps, such as the deep inferior epigastric artery perforator flap. 41 However, the outcomes of these various techniques are not yet well-established, and no technique has emerged as the optimal solution.…”
Section: Introductionmentioning
confidence: 99%